Олександр Палладін на посту президента АН УРСР (1946—1962): кроки академічних інститутів до переднього краю світової науки - Гамалія, В.М. (Наука та наукознавство, 2019)
У статті розглядаються стан і характерні риси української академічної науки повоєнних років у період перебування О.В. Палладіна на посту президента АН УРСР. Досліджено життєвий та творчий шлях вченого, створення ним наукової школи, його організаційну та викладацьку роботу. В статье рассматриваются состояние и характерные особенности украинской академической науки послевоенных лет в период пребывания А.В. Палладина на посту президента АН УССР. Исследуется жизненный и творческий путь ученого, создание им науч ной школы, организационная и преподавательская работа. The article offers a review of the state and characteristics of the Academy sector of the Ukrainian science & technology system in the post-war years during O.V. Palladin’s activities as President of the Academy of Sciences of Ukrainian SSR (1946–1962), which helped establish an underlying principle of comparative-evolutionary field in biochemistry: the principle of biochemical unity of the organic world. The Palladin’s contribution to biochemistry gives grounds to position him as a founder of the modern biochemical science.